Water Monitoring of Aquatic Plant Ponds and Selected Species as Phytoremediator in Purwodadi Botanic Garden - Irawanto, Rony; Apriliani , Adini; Yanuwiadi, Bagyo; Leksono, Amin Setyo; Soemarno, Soemarno (Postgraduate School of Universitas Brawijaya, 2025)
Purwodadi Botanic Garden is one of the botanic gardens in Indonesia, located in Pasuruan, East Java. Purwodadi Botanic Garden (PBG) is an ex-situ plant conservation area that serves five main functions: conservation, research, education, ecotourism, and environmental services. Purwodadi Botanic Garden features a living collection of plants, primarily terrestrial, but also includes aquatic species. Therefore, this study aims to conduct water quality monitoring in aquatic plant ponds and present the experiments of phytoremediation on selected species of aquatic plants. This research employs a mixed-methods approach, combining qualitative and quantitative methods. Data were obtained from direct observation of aquatic plants in the garden, monthly monitoring of water quality in 32 ponds, and the results of phytoremediation experiments from research activities spanning over ten years. Monitoring water quality using water-test kits is inexpensive, easy to use, and yields results quickly. Parameters measured for environmental quality are temperature, humidity, light intensity, pH, TDS, and water temperature. The results show that, out of 32 ponds in the garden, only 12 ponds were found to have aquatic plants. The water quality in ponds with aquatic plants is generally better than in those without aquatic plants, indicating that the aquatic plants in ponds act as phytoremediators in the effort to improve water quality. Purwodadi Botanic Garden contains 25 species of aquatic plants. However, during the observation of the pond, only 15 species of aquatic plants were present. The results of the experiments selected 10 species as phytoremediation agents for both organic and inorganic pollution. The 10 species are Acanthus ilicifolius, Actinoscirpus grossus, Ceratophyllum demersum, Coix lacryma-jobi, Echinodorus radicans, Lemna minor, Ludwigia octovalvis, Pistia stratiotes, Sagittaria lancifolia, and Salvinia molesta. Keywords: aquatic, garden, phytoremadiation, plant, water